The quality of mortality data of the 2010 Census of Argentina - Sacco, Nicolás (2016)
Objective: to evaluate the available variables of mortality from the last population census in Argentina. Methods: it is based on indirect estimation methods which provide a reading of the quality of these statistics in comparison with previous censuses and vital statistics. Results: The rates of child and adult mortality compared with birth and death rates show that this data does not reveal serious problems of quality or coverage and the level (and trend) indicated by the sources is widely supported. Discusion: although the results seem to show consistency, the ability to detect and quantify the errors remains a blind spot until all of the necessary information is published for a thorough examination, given the limited universe of publications by the National Institute of Statistics of Argentina. Conclusion: the mortality population estimates are consistent with previous census data from 2001 and with estimates of births and deaths from the intercensal period.